Eletrophilic Chemistry of Tranilast Is Involved in Its Anti-Colitic Activity via Nrf2-HO-1 Pathway Activation - Seongkeun Jeong; Changyu Kang; Sohee Park; Sanghyun Ju; Jin-Wook Yoo; In-Soo Yoon; Hwayoung Yun; Yunjin Jung (MDPI AG, 2021)
Tranilast (TRL), a synthetic derivative of a tryptophan metabolite, is an anti-allergic drug used to treat bronchial asthma. We investigated how TRL activated the nuclear factor-erythroid 2 p45-related factor 2 (Nrf2)-hemeoxygenase-1 (HO-1) pathway based on the electrophilic chemistry of the drug and whether TRL activity contributed to the treatment of rat colitis. In human colon carcinoma cells, TRL activated Nrf2, as represented by an increase in nuclear Nrf2 and induction of Nrf2-dependent luciferase and, subsequently, HO-1, a target gene product of Nrf2. TRL activation of Nrf2 and induction of HO-1 were completely prevented by chemical reduction of the electrophilic functional group (α, β-unsaturated carbonyl group) in the drug. In parallel, TRL was reactive with the nucleophilic thiol group in N-acetylcysteine, forming a covalent adduct. Moreover, TRL, but not reduced TRL, binds to Kelch-like ECH-associated protein 1 (KEAP1), releasing Nrf2. TRL administration ameliorated colonic damage and inflammation in rats with dinitrobenzene sulfonic acid-induced colitis, which was partly compromised by the chemical reduction of TRL or co-treatment with an HO-1 inhibitor. Our results suggest that TRL activated the Nrf2-HO-1 pathway via covalent binding to KEAP1, partly contributing to TRL amelioration in rat colitis.